2020
DOI: 10.1111/clr.13654
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation on metal alloys, zirconia and polyetherketoneketone as implant materials in vivo

Abstract: Objectives This study investigated biofilm formation on discs of metal alloys, zirconia and polyetherketoneketone in vivo. Material and Methods Sixteen healthy volunteers conducted two runs of 24 hr each wearing an intraoral splint with 15 discs representing five different materials (gold‐based [EL] and silver‐based [PA] noble metal alloys; zirconia [ZR]; polyetherketoneketone [PEKK]; titanium zirconium alloy [TiZr]). Safranin staining assays and colony‐forming unit (CFU) counts were conducted. Linear mixed‐ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…Another consideration is that the test devices of the present study had a mixed coating of Bi and Ga, while the discs in the study by Cochis et al, (2015) were treated with Ga ions. In another in vivo study in 16 volunteers, Zeller et al, (2020) investigated plaque formation on discs of metal alloys, zirconia (Zr)…”
Section: Godoymentioning
confidence: 99%
See 2 more Smart Citations
“…Another consideration is that the test devices of the present study had a mixed coating of Bi and Ga, while the discs in the study by Cochis et al, (2015) were treated with Ga ions. In another in vivo study in 16 volunteers, Zeller et al, (2020) investigated plaque formation on discs of metal alloys, zirconia (Zr)…”
Section: Godoymentioning
confidence: 99%
“…It was reported that less plaque was formed on discs made of either gold-or silver-based alloys than discs produced from Zr, PEKK or titanium-zirconium alloy. Similar to the study by Cochis et al, (2015), Zeller et al, (2020) evaluated plaque formation over 24 hr and, hence, no information is available whether the potential antibacterial effects of silver or gold alloys were sustained overtime.…”
Section: Godoymentioning
confidence: 99%
See 1 more Smart Citation
“…However, like other polymers, fumes resulted from overheating of PEEK can be harmful [ 57 ]. The biofilm formation on PAEK implant structures were lower than that on zirconia or Ti implant components [ 60 , 61 ]. Mucosal response to PEEK as a prosthodontic material was good [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“… 15 16 Furthermore, they are easily obtained in personalized (3D) forms, thus propitiating the manufacture of radiolucent prostheses with good biomechanical properties, and accumulate less biofilm than ceramics and metallic alloys, which are usual materials in restorative dentistry. 17 In vitro studies and short-term clinical reports have evaluated the use of PEKK 13 and PEEK in dentistry for implant supported dental prosthesis. 18 However, their comparative biomechanical behavior as framework for full-arch fixed dental prosthesis is still not well understood.…”
Section: Introductionmentioning
confidence: 99%